Survey and disease surveillance of newly introduced L.VANNAMEI (Boone, 1931) in India. - Roshan Maria Peter (Department of Aquaculture, College of Fisheries, 2011)
P. monodon (tiger shrimp) was the most preferred cultured species in India, but repeated occurrence of diseases especially white spot disease (WSD) caused by white spot syndrome virus (WSSV) had a severe setback to the shrimp culture industry. This prompted the industry to actively promote the introduction of a non-native species, the Pacific white shrimp, Litopenaeus vannamei, as an alternative to P. monodon for commercial aquaculture operations in the country. The authority to issue licenses to take up L.vannamei culture was vested with the Coastal Aquaculture Authority (CAA), who issued licenses for 1,208 aqua farmers in 2009. Availability of SPF stock, ability to grow well even at high stocking densities, reduced days of culture (DOC), lesser protein requirement (28-35%) and demand in the international market attracted aquafarmers to switch to culture of L.vannamei. A survey carried out in the Nellore district of Andhra Pradesh to understand the level of acceptance and the nature of culture practice among the farms culturing L.vannamei revealed that only 33% of the farms surveyed had obtained permission from the CAA, 41% followed biosecurity measures and merely 10% had the facility for Effluent Treatment System. 53% practised chlorination and de-chlorination of water during water exchange and only 38% farms maintained trained personnel. It was observed during the survey that only 84% procured tested SPF seed from certified hatcheries. While 90-92% of yhe farms depended on pelleted feed, only 80-85% of the farms surveyed carried out regular monitoring every 1-2 weeks. Disease surveillance in the farms surveyed did not detect the presence of any of the major shrimp viruses (WSSV, IHHNV, MBV, HPV and TSV) in the 60 samples screened using molecular methods. However, Vibrio sp. was detected in samples exhibiting obvious signs of bacterial disease. High stocking densities without adequate number of aerators can be stressful to the shrimps and might be the reason for bacterial infection. Economic analysis indicates that L.vannamei culture is more profitable than P.monodon culture.